Low-friction and wear-resistant polyether-ether-ketone material and preparation method thereof

By grafting the hydrophilic polymer brush on the PEEK powder and performing hot pressing molding, the problem of serious wear of pure PEEK materials under long service is solved, the low friction and wear resistance of the modified PEEK materials are achieved, and the service life of the artificial joint prosthesis is extended.

CN119708375AActive Publication Date: 2025-03-28CHINA UNIV OF MINING & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411905621.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Pure polyether ether ketone (PEEK) materials cannot achieve ultra-low wear under long service, limiting their service life as artificial joint prosthesis.

Method used

The modified PEEK material with an integral hydrophilic polymer brush structure is formed by grafting the hydrophilic polymer brush brush on the PEEK powder and then undergoing hot pressing.

Benefits of technology

It improves the overall wetting and wear resistance of PEEK materials, achieves long-term low friction and wear resistance, and extends the service life of artificial joint prosthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708375A_ABST
    Figure CN119708375A_ABST
Patent Text Reader

Abstract

The invention discloses a low-friction and wear-resistant polyether-ether-ketone material and a preparation method thereof. The preparation method comprises the following steps: dissolving an SPMK monomer in a methanol solution to prepare a modified solution with the molar concentration of 0.3-0.7 mol / L; pEEK powder is soaked in the modified solution, stirring is conducted for 5-10 h under a high-pressure mercury lamp, and light-induced graft polymerization is conducted to obtain modified powder; filtering, respectively carrying out ultrasonic cleaning on the filtered modified powder by using absolute ethyl alcohol and deionized water, drying in a drying oven at 60 DEG C for 24 hours after ultrasonic cleaning, and storing; filling the modified powder into a mould of 0.4 * 10 * 10 cm; loading the mold filled with the modified powder for 1 hour under 10MPa by using a press vulcanizer, then unloading, raising the temperature of each clamping plate of the press vulcanizer to 350-370 DEG C under no load, raising the clamping plates to enable the mold to be loaded to 10MPa, keeping the temperature for 5-60 minutes, then turning off the power supply of the press vulcanizer, cooling to room temperature in a pressure maintaining state, and then taking out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a low-friction, wear-resistant polyetheretherketone material and a preparation method thereof. Background Art

[0002] Bone and joint diseases caused by congenital and acquired factors not only bring serious inconvenience to patients' daily lives, but also bring physical and mental pain. At this time, joint replacement is needed. Traditional artificial joint replacement materials mainly include medical metal materials such as titanium alloy, cobalt-chromium-molybdenum, etc. and medical polymer materials such as ultra-high molecular weight polyethylene and polyethylene. These artificial joints are prone to severe wear, metal ion toxicity release, bone tissue dissolution and other problems during long-term service, which affect the service life of artificial joints. Polyetheretherketone PEEK has excellent mechanical strength, good wear resistance, elastic modulus close to human bones and good biocompatibility, and is widely used in the field of artificial joint replacement. However, pure PEEK material cannot achieve ultra-low wear under long-term service, which limits its service life as an artificial joint prosthesis. Therefore, it is necessary to modify the PEEK material to improve its wear resistance.

[0003] The shallow layer of natural cartilage is believed to contain proteoglycans, which can be combined with hyaluronic acid to form a surface brush-like structure that can absorb water and hydrate and lubricate. In recent years, inspired by natural cartilage, it has become a common method to graft hydrophilic polymer brushes on the surface of PEEK materials to improve surface wettability and lubricity. However, when it is used as an artificial joint prosthesis material, once the surface polymer brush wear-resistant layer is destroyed and the matrix material is exposed to the surface, the wear resistance of the material will decrease rapidly, and it cannot meet the needs of long-term use of artificial joints. Therefore, the present application proposes a new modification method of first modifying and then molding, by photo-grafting modification of PEEK powder, grafting hydrophilic polymer brushes on PEEK powder, and after hot pressing molding, the whole PEEK material has a hydrophilic polymer brush structure, which improves the overall wear resistance of the material, which is of great significance for the development of extending the sliding interface of PEEK material artificial joints. Summary of the invention

[0004] Technical issues solved:

[0005] The purpose of the present invention is to overcome the technical problems existing in the prior art that pure PEEK materials cannot achieve ultra-low wear under long-term service and cannot meet the needs of long-term use of artificial joints. The present application provides a low-friction, wear-resistant polyetheretherketone material and a preparation method.

[0006] Technical solution:

[0007] To achieve the above objectives, this application is implemented through the following technical solutions:

[0008] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0009] Step 1: dissolving SPMK monomer in methanol solution to prepare a modified solution with a molar concentration of 0.3-0.7 mol / L;

[0010] Step 2: immerse 3 g of PEEK powder in 40-60 mL of the modified solution according to the mass volume ratio, stir for 5-10 h under a high-pressure mercury lamp, and perform photoinduced graft polymerization to obtain a modified powder;

[0011] Step 3: filtering the modified powder obtained in step 2, ultrasonically cleaning the filtered modified powder with anhydrous ethanol and deionized water respectively, drying the powder in an oven at 40-60° C. for 12-24 hours and then storing the powder;

[0012] Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold;

[0013] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 5-10MPa for 0.5-1h, then unload it, heat each clamp of the flat-plate vulcanizer to 350-370℃ under no-load, raise the clamp to load the mold to 5-10MPa, keep warm for 5-60min, turn off the power of the flat-plate vulcanizer, cool to room temperature under pressure and take it out.

[0014] Preferably, the methanol solution in step 1 is 99.5% methanol solution.

[0015] Preferably, in the step 1, 24.632 g of SPMK monomer is dissolved in 200 mL of methanol solution according to a mass-to-volume ratio to prepare a modified solution with a molar concentration of 0.5 mol / L.

[0016] Preferably, the high-pressure mercury lamp in step 2 is a 250W high-pressure mercury lamp with a central wavelength of 365nm.

[0017] Preferably, in the step 2, 12 g of PEEK powder is immersed in the modified solution prepared in the step 1 according to the mass volume ratio.

[0018] Preferably, in step 2, the stirring speed is 600 r / min and the stirring is performed for 8 hours.

[0019] Preferably, the filtering condition in step three is vacuum filtration using 20-mesh filter paper.

[0020] Preferably, the ultrasonic cleaning frequency in step three is 40 kHz and the cleaning time is 20 min.

[0021] Preferably, in step three, the mixture is dried in an oven at 60° C. for 24 hours.

[0022] Preferably, in step 5, the mold containing the modified powder is loaded at 10 MPa for 1 hour and then unloaded. After heating each clamping plate of the flat vulcanizer to 350° C. under no-load, the clamping plate is raised to load the mold to 10 MPa and kept warm for 30 minutes.

[0023] The technical principle of the present invention is: the present application uses a high-pressure mercury lamp with a central wavelength of 365nm to irradiate PEEK powder at room temperature to induce polymerization reaction, and then grafts a hydrophilic polymer brush 3-sulfopropyl methacrylate potassium salt (SPMK) on the PEEK powder and then reshapes it. Because the sulfonic acid group with negative charge on the side chain of SPMK has excellent hydration lubrication ability, it helps to lubricate the synovial fluid in the joint cavity. By grafting a hydrophilic polymer brush on the powder and then reshaping it, the surface and interior of the PEEK material have a hydrophilic polymer brush, thereby improving the overall wettability and wear resistance of the PEEK material, so as to obtain a PEEK material with long-term low friction and wear resistance.

[0024] Beneficial effects:

[0025] The present application provides a low-friction, wear-resistant polyetheretherketone material and a preparation method, which have the following beneficial effects:

[0026] 1. The present invention improves the overall wettability and wear resistance of the PEEK material by grafting a hydrophilic polymer brush onto the PEEK powder and then molding it, so as to obtain a PEEK material with long-term low friction and wear resistance;

[0027] 2. The present invention directly grafts the SPMK hydrophilic polymer brush onto the PEEK powder. After hot pressing, the powder not only has the hydrophilic polymer brush on the surface, but also has the hydrophilic polymer brush structure inside.

[0028] 3. Compared with pure PEEK and surface-modified PEEK materials, after the hydrophilic polymer brush wear-resistant layer on the surface of the modified PEEK material proposed by the present invention is destroyed, the internal polymer brush can also play a role in reducing friction and wear resistance, and has a lower wear rate and a longer service life;

[0029] 4. The hot pressing molding process proposed in the present invention can discharge the gas in the powder gap in the mold by pre-loading and then idling. The internal pores of the obtained PEEK plate are less than those of the PEEK plate directly loaded with heating and heat insulation molding, and the strength and stability of the material are better. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of preparation and hot pressing of modified polyetheretherketone powder in this application;

[0031] Figure 2is the X-ray photoelectron spectrum of the modified polyetheretherketone powder in the present application;

[0032] Figure 3 The mechanical properties of the modified polyetheretherketone product and the pure polyetheretherketone product in this application are shown in Figure 1, wherein (a) is the stress-strain curve; (b) is the compression modulus; (c) is the hardness;

[0033] Figure 4 The tribological performance diagram of the modified polyetheretherketone product and the pure polyetheretherketone product in this application, wherein (a) is the friction coefficient; (b) is the wear rate; and (c) is the scanning electron microscope image of the wear scar. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments, and cannot be understood as limiting the scope of protection of the present invention. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0035] Manufacturers and models of raw materials in this application: PEEK is polyetheretherketone, purchased from Jilin Zhongyan Polymer Materials Co., Ltd., model 770PF; SPMK is 3-sulfonic acid propyl methacrylate potassium salt, purchased from Aladdin Reagent, product number S107131; methanol was purchased from Macklin Reagent, product number M813895;

[0036] Ethanol was purchased from Shanghai Lingfeng Chemical Reagent Co., Ltd. with the product number E101501.

[0037] Example 1

[0038] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0039] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0040] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 5 h under the central wavelength of 365 nm of a 250 W high-pressure mercury lamp, and perform photoinduced graft polymerization to obtain modified powder;

[0041] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0042] Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold;

[0043] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 60 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0044] Example 2

[0045] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0046] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0047] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0048] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0049] Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold;

[0050] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 60 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0051] Example 3

[0052] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0053] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0054] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 10 h under the central wavelength of 365 nm of a 250 W high-pressure mercury lamp, and perform photoinduced graft polymerization to obtain modified powder;

[0055] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0056] Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold;

[0057] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 60 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0058] Example 4

[0059] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0060] Step 1: dissolve 14.779 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.3 mol / L;

[0061] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0062] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0063] Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold;

[0064] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 60 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0065] Example 5

[0066] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0067] Step 1: dissolve 34.484 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.7 mol / L;

[0068] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0069] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0070] Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold;

[0071] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 60 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0072] Example 6

[0073] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0074] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0075] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0076] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0077] Step 4: Take 60 g of the completely dried modified powder and put it into a 0.4×10×10 cm mold;

[0078] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 30 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0079] Example 7

[0080] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0081] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0082] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0083] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0084] Step 4: Take 60 g of the completely dried modified powder and put it into a 0.4×10×10 cm mold;

[0085] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 5 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0086] Example 8

[0087] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0088] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0089] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0090] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0091] Step 4: Take 60 g of the completely dried modified powder and put it into a 0.4×10×10 cm mold;

[0092] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 360°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 30 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0093] Example 9

[0094] A method for preparing a low-friction, wear-resistant polyetheretherketone material comprises the following steps:

[0095] Step 1: dissolve 24.632 g of SPMK monomer in 200 mL of 99.5% methanol solution to prepare a modified solution with a molar concentration of 0.5 mol / L;

[0096] Step 2: immerse 12 g of PEEK powder in the modified solution according to the mass volume ratio, stir for 8 h under a 250 W high pressure mercury lamp with a central wavelength of 365 nm, and perform photoinduced graft polymerization to obtain modified powder;

[0097] Step 3: The modified powder obtained in step 2 is vacuum filtered with a 20-mesh filter paper, and the filtered modified powder is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then dried in an oven at 60° C. for 24 hours and stored;

[0098] Step 4: Take 60 g of the completely dried modified powder and put it into a 0.4×10×10 cm mold;

[0099] Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 350°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 30 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0100] Comparative Example 1

[0101] A method for preparing a PEEK material comprises the following steps:

[0102] Step 1: Weigh 60g of pure PEEK powder and place it in a 60℃ oven for drying for 24h before storing;

[0103] Step 2: Weigh 60 g of the completely dried pure PEEK powder and put it into a 0.4×10×10 cm mold;

[0104] Step 3: Use a flat-plate vulcanizer to load the mold containing pure PEEK powder in step 2 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 370°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 60 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0105] Comparative Example 2

[0106] A method for preparing a PEEK material comprises the following steps:

[0107] Step 1: Weigh 60g of pure PEEK powder and place it in a 60℃ oven for drying for 24h before storing;

[0108] Step 2: Weigh 60 g of the completely dried pure PEEK powder and put it into a 0.4×10×10 cm mold;

[0109] Step 3: Use a flat-plate vulcanizer to load the mold containing pure PEEK powder in step 2 at 10 MPa for 1 hour, then unload it. After heating each clamping plate of the flat-plate vulcanizer to 350°C under no-load, raise the clamping plate to load the mold to 10 MPa. After keeping warm for 30 minutes, turn off the power of the flat-plate vulcanizer, cool it to room temperature under pressure and take it out.

[0110] Table 1 Process parameters of Examples 1 to 10 and Comparative Examples 1 to 2

[0111]

[0112] The mechanical and tribological properties of the PEEK samples obtained in the above Examples 1 to 9 and Comparative Examples 1 to 2 were tested, and the wear morphology after friction was detected.

[0113] In order to evaluate the effects of different irradiation times and modification concentrations on the modification effect of PEEK powder, the modified PEEK powders obtained in Examples 1 to 5 were characterized using X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Figure 2 As shown. Figure 2 The results show that the peak at 167eV of the modified powder with a modification concentration of 0.5mol / L and an illumination time of 8h belongs to the -SO3-C group, while this phenomenon is not observed in pure PEEK powder, indicating that SPMK was successfully grafted onto PEEK powder.

[0114] In order to evaluate the effects of different hot pressing processes on the mechanical properties of PEEK, the PEEK samples obtained in Example 2, Examples 6 to 9 and Comparative Examples 1 to 2 were subjected to hardness and compression tests using a Shore hardness tester and an electronic universal testing machine. Figure 3 shown. Figure 3 The results show that the hardness of the PEEK sample at a holding temperature of 350℃ and a holding time of 30min is 92.5HD and the compression modulus is 18.43MPa, indicating that the modified PEEK plate still has good mechanical properties and meets the mechanical requirements of joint prostheses.

[0115] In order to evaluate the tribological properties of the PEEK samples prepared in Example 2, Examples 6-9 and Comparative Examples 1-2, the three groups of samples were subjected to friction tests on a micro friction and wear tester, and the wear scar morphologies left after friction of the three groups of samples were characterized by scanning electron microscopy and atomic force microscopy, as shown in FIG. Figure 4 As shown in the figure, the modified PEEK sample prepared in Example 9 has a lower friction coefficient and wear rate, and the wear degree of the wear scar surface is lower, which is beneficial to improving the wear resistance of the sliding interface of the joint prosthesis and extending the service life of the prosthesis.

[0116] The above embodiments and comparative examples are only for explaining the principle and effect of the present invention, and are not intended to limit the present invention. It should be noted that, for those skilled in the art, without violating the spirit and scope of the present invention, the above embodiments may be modified or improved, and such modifications or improvements shall also be deemed as the protection scope of the present invention.

Claims

1. A method for preparing a low-friction, wear-resistant polyetheretherketone material, characterized in that: The following steps are involved: Step 1: dissolving SPMK monomer in methanol solution to prepare a modified solution with a molar concentration of 0.3-0.7 mol / L; Step 2: immerse 3 g of PEEK powder in 40-60 mL of the modified solution according to the mass volume ratio, stir for 5-10 h under a high-pressure mercury lamp, and perform photoinduced graft polymerization to obtain a modified powder; Step 3: filtering the modified powder obtained in step 2, ultrasonically cleaning the filtered modified powder with anhydrous ethanol and deionized water respectively, drying the powder in an oven at 40-60° C. for 12-24 hours and then storing the powder; Step 4: Place the completely dried modified powder into a 0.4×10×10 cm mold; Step 5: Use a flat-plate vulcanizer to load the mold containing the modified powder in step 4 at 5-10MPa for 0.5-1h, then unload it, heat each clamp of the flat-plate vulcanizer to 350-370℃ under no-load, raise the clamp to load the mold to 5-10MPa, keep warm for 5-60min, turn off the power of the flat-plate vulcanizer, cool to room temperature under pressure and take it out.

2. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: The methanol solution in step 1 is 99.5% methanol solution.

3. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: In the step 1, 24.632 g of SPMK monomer is dissolved in 200 mL of methanol solution according to the mass-to-volume ratio to prepare a modified solution with a molar concentration of 0.5 mol / L.

4. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: The high-pressure mercury lamp in step 2 is a 250W high-pressure mercury lamp with a central wavelength of 365nm.

5. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: In the step 2, 12 g of PEEK powder is immersed in the modified solution prepared in the step 1 according to the mass volume ratio.

6. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: In the step 2, the stirring speed is 600 r / min and the stirring is performed for 8 hours.

7. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: The filtering condition in the step 3 is vacuum filtration using 20-mesh filter paper.

8. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: In the step 3, the ultrasonic cleaning frequency is 40 kHz and the cleaning time is 20 min.

9. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: In the step 3, the mixture is dried in an oven at 60° C. for 24 hours.

10. The low-friction, wear-resistant polyetheretherketone material and preparation method according to claim 1, characterized in that: In the step 5, the mold containing the modified powder is loaded at 10 MPa for 1 hour and then unloaded. After the clamping plates of the flat vulcanizer are heated to 350° C. under no-load, the clamping plates are raised to load the mold to 10 MPa and kept warm for 30 minutes.

Citation Information

Patent Citations

  • Preparation method of ultra high molecular weight polyethylene bulletproof helmet

    CN102528998A

  • Low-friction polyether-ether-ketone artificial cotyle and manufacturing method thereof

    CN105169490A

  • Method of sintering zirconia ceramics under oscillation pressure in ultrasonic-assisted mode

    CN107954714A

  • Artificial joint component, preparation method thereof and friction pair

    CN113995886A

  • Modified polyether-ether-ketone powder, modification method, polyether-ether-ketone product and preparation method

    CN114957649A